Pendampingan Psikoedukasi Terhadap Anak Pasca Bencana Hidrometeorologi Di Aceh Utara - Linur Ficca Agustina; Maya Safitri; Nurmala Nurmala; Oknita Oknita (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2026)
Hydrometeorological disasters such as floods and landslides that frequently strike North Aceh region have significant psychological impacts on children, including post-traumatic stress disorder (PTSD), anxiety, depression, and behavioral regression. This community service activity aimed to provide psychoeducational assistance to children following hydrometeorological disasters in Dewantara and Muara Batu Districts, North Aceh Regency. The method used was community-based psychoeducation, encompassing needs assessment, group psychoeducation sessions, therapeutic play, and training for parents and teachers. The activity was conducted over four weeks involving 85 children aged 6–15 years affected by the disaster. Results indicated a significant reduction in post-traumatic stress symptoms in 72% of participants, improved emotional regulation abilities, and enhanced understanding among parents and teachers regarding post-disaster psychological support. This program was effective in restoring children's psychological condition and strengthening community capacity in providing psychosocial support after disasters